Case Report: Application of Thoracoscopic Clamp Radiofrequency Ablation on Atrial Tachycardia Originating From Right Atrial Appendage After Catheter Ablation Failure - Luo, Li; Qin, Zuoan; Shi, Ruizheng; Ge, Liangqing (Frontiers in Cardiovascular Medicine, 2021)
Atrial tachycardia originating from the right atrial appendage has a higher probability of failure of catheter ablation. Here we report a case of a 13-year-old boy with incessant tachycardia, complicated by heart enlargement and heart failure. Electrophysiological examination showed that atrial tachycardia (AT) originated from the apex of the right atrial appendage, and endocardial catheter ablation was ineffective. After thoracoscopic approach, the right atrial appendage was successfully ablated with bipolar radiofrequency ablation forceps, atrial tachycardia was terminated and sinus rhythm was restored. Within 3 months since the patient was discharged from the hospital, no arrhythmia occurred and the heart structure returned to normal. Thus, thoracoscopic clamp radiofrequency ablation may be a reasonable choice for young patients with atrial tachycardia originated from the right atrial appendage when transendocardial ablation is not effective.